Bias and representativeness in digitized newspaper collections: Introducing the environmental scan. (14th July 2022) - Beelen, Kaspar; Lawrence, Jon; Wilson, Daniel C S; Beavan, David
Abstract: This article introduces the 'Environmental Scan' as answer to the question of hidden biases in digital heritage collections. Its substantive focus is digitized nineteenth-century British provincial newspapers, and in particular the JISC corpus, a popular, publicly-funded resource for scholars. While multiple papers have meticulously investigated the genesis of such newspaper collections, in the process highlighting the often unacknowledged politics of collection, preservation and dissemination via microfilm and now digitization, our aim is to explore questions of representativeness and bias in new ways by enriching computational analysis of digital corpora with the historical insights that can be derived from a contemporaneous reference source: namely, the Victorian newspaper press directories.